From corporate corruption to Rentiership: extending Box’s Power, Crime and Mystification - Bittle, Steven (Demystifying power, crime and social harm, 2023)
This chapter explores Box’s arguments about law and the mystification of crime through a critical examination of recent efforts across the public and private sectors that takes corporate corruption as problematic and in need of elimination. In addition to examining how the “anti-corruption” movement has effectively constrained what constitutes corruption, therein glossing over the predatory instincts of global capitalism, we consider how these measures (re)produce as legitimate and natural a parasitic and anti-democratic form of wealth extraction known as rentiership. In so doing, we extend and update Box’s ideas by noting an affinity with Pierre Bourdieu’s theory of social action. Our goal is to provide a theoretical grounding for understanding and explaining corruption as a crime of the powerful and, importantly, avoid naïve and untenable explanations based on self-interest and rational choice theory.